The illustration guidebook of making Tie Dye batik technique / Nur Hakimah ‘Aliah Mohamad Nazri and Rafuzan Jaafar - Mohamad Nazri, Nur Hakimah ‘Aliah; Jaafar, Rafuzan (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
The purpose of writing this article is to make an illustration guidebook of The Making Tie Dye Batik Technique where it will discuss the creative process of making a guidebook with illustrations of technique tie dye batik that are easily understood by the target audience. This design is convenient and dedicated towards the Ministry of Tourism, Arts and Culture. The purpose of writing this article is to make an illustration guidebook of The Making Tie Dye Batik Technique where it will discuss the creative process of making a guidebook with illustrations of technique tie dye batik that are easily understood by the target audience. This design is convenient and dedicated towards the Ministry of Tourism, Arts and Culture.